2015
DOI: 10.1007/s00394-015-0922-1
|View full text |Cite
|
Sign up to set email alerts
|

Does a diet low in FODMAPs reduce symptoms associated with functional gastrointestinal disorders? A comprehensive systematic review and meta-analysis

Abstract: The present meta-analysis supports the efficacy of a low FODMAP diet in the treatment of functional gastrointestinal symptoms. Further research should ensure studies include dietary adherence, and more studies looking at greater number of patients and long-term adherence to a low FODMAP diet need to be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
251
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(274 citation statements)
references
References 50 publications
11
251
2
10
Order By: Relevance
“…A meta-analysis on low-FODMAP diet from 2015 including 6 randomized controlled trials (RCT) and 16 nonrandomized interventional studies found a significant decrease in IBS symptom severity scores for abdominal bloating, pain and diarrhea and significantly improved quality of life scores in 70% of patients. 89 The drawbacks of low FODMAP diets are the high levels of dietary restrictions, the need for monitoring by an expert dietitian to prevent inappropriate weight-loss, over-restrictive or inappropriate diets, and potential nutritional deficiencies. 90 The major products of FODMAPs fermentation are short chain fatty acids (SCFA), and some major microbial SCFA-producers may be altered in IBS.…”
Section: Diet and Ibsmentioning
confidence: 99%
“…A meta-analysis on low-FODMAP diet from 2015 including 6 randomized controlled trials (RCT) and 16 nonrandomized interventional studies found a significant decrease in IBS symptom severity scores for abdominal bloating, pain and diarrhea and significantly improved quality of life scores in 70% of patients. 89 The drawbacks of low FODMAP diets are the high levels of dietary restrictions, the need for monitoring by an expert dietitian to prevent inappropriate weight-loss, over-restrictive or inappropriate diets, and potential nutritional deficiencies. 90 The major products of FODMAPs fermentation are short chain fatty acids (SCFA), and some major microbial SCFA-producers may be altered in IBS.…”
Section: Diet and Ibsmentioning
confidence: 99%
“…10,13,25 Details of the types of studies and their specific results are shown in the Table. Such studies as well as those published in abstract form were subjected to a recent meta-analysis and systematic review, with the conclusion that the diet is effective in patients with IBS. 28 The outcomes of such studies have also prompted the increasing need to translate the diet for practical use by other countries. 25 The greatest improvement in overall gastrointestinal symptoms appears to occur within 7 days of adhering to a low FODMAP diet, after which symptoms remain relatively constant.…”
Section: Efficacy Of the Low Fodmap Dietmentioning
confidence: 99%
“…Publication of two recent systematic reviews confirms the growing research interest in the area (112,113) .…”
Section: Clinical Effectiveness Of the Low Fodmap Dietmentioning
confidence: 71%